FORMULASI DAN UJI AKTIVITAS MASKER GEL PEEL-OFF ANTIJERAWAT EKSTRAK ETANOL BAWANG DAYAK (Eleutherina palmifolia (L.) Merr) TERHADAP BAKTERI Staphylococcus aureus SECARA IN VITRO - Husnani Husnani; Fitri Sri Rizki (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Dayak union contains compounds group of alkaloids, flavonoids, saponins, tannins, glycosides, and triterpenoids which have antiacne effect. The aim of this research was to provide peel-off mask gel formula from ethanol extract of dayak union and tested its physical properties and their antibacteria activities to Staphylococcus aureus. Peel-off mask gel formulation from extract of dayak union made with various extract concentrasion which are 50 mg/ml, 75 mg/ml dan 100 mg/ml with Polyvinyl Alcohol (PVA) base as gelling agent that has adhesive properties or could make flim layer thatt could peel off after its dried. Peel-off mask gel tested its physical properties, which are organoleptic, homogenity, pH, spread capacity, drying time and viscosity. The results of physical evaluation obtained that 1st formula has calm texture, brown-red colour and unique scent of dayak union, viscosity 60.666 cps, drying time for 725,67 seconds, spread capacity 4.49 cm, and pH 5. Results of antiacne activity shows that 1st formula is more effective that 2nd and 3rd formula, with inhibition zone diameter to Staphylococcus aureus is 0.87 cm. So it conclude that 1st formula is the best formula y ist physical and can give inhibition zone on the growth of Staphylococcus aureus.